Combined TRPC3 and TRPC6 blockade by selective small-molecule or genetic deletion inhibits pathological cardiac hypertrophy - Seo, Kinya (2014)
Chronic neurohormonal and mechanical stresses are central fea-tures of heart disease. Increasing evidence supports a role forthe transient receptor potential canonical channels TRPC3 andTRPC6 in this pathophysiology. Channel expression for both is nor-mally very low but is increased by cardiac disease, and geneticgain- or loss-of-function studies support contributions to hypertro-phy and dysfunction. Selective small-molecule inhibitors remainscarce, and none target both channels, which may be useful giventhe high homology among them and evidence of redundant sig-naling. Here we tested selective TRPC3/6 antagonists (GSK2332255Band GSK2833503A; IC50,3–21 nM against TRPC3 and TRPC6) andfound dose-dependent blockade of cell hypertrophy signaling trig-gered by angiotensin II or endothelin-1 in HEK293T cells as well as inneonatal and adult cardiac myocytes. In vivo efficacy in mice andrats was greatly limited by rapid metabolism and high protein bind-ing, although antifibrotic effects with pressure overload were ob-served. Intriguingly, although gene deletion of TRPC3 or TRPC6alone did not protect against hypertrophy or dysfunction frompressure overload, combined deletion was protective, support-ing the value of dual inhibition. Further development of thispharmaceutical class may yield a useful therapeutic agent forheart disease management.